Outcomes of orthopaedic trauma patients undergoing surgery during the peak period of COVID-19 infection at a UK major trauma centre. Issue 5 (October 2021) - Hope, Natalie; Gulli, Valeria; Hay, Daniel; Tahmassebi, Ramon; Vasireddy, Aswinkumar; Tavakkolizadeh, Adel; Colegate-Stone, Toby
Abstract: Background: To review the clinical outcomes of all patients undergoing emergency orthopaedic trauma surgery at a UK major trauma centre during the first 6 weeks of the COVID-19 related lockdown. Methods: A retrospective review was performed of all patients who underwent emergency orthopaedic trauma surgery at a single urban major trauma centre over the first six-week period of national lockdown. Demographics, co-morbidities, injuries, injury severity scores, surgery, COVID-19 status, complications and mortalities were analysed. Results: A total of 76 patients were included for review who underwent multiple procedures. Significant co-morbidity was present in 72%. The overall COVID-19 infection rate of the study population at any time was 22%. Sub-group analysis indicated 13% had active COVID-19 at the time of surgery. Only 4% of patients developed COVID-19 post surgery with no mortalities in this sub-group. The overall mortality rate was 4%. The overall complication rate was 14%. However mortality and complications rates were higher if the patients had active COVID-19 at surgery, if they were over 70 years and had sustained life-threatening injuries. Conclusion: The overall survival rate for patients undergoing emergency orthopaedic trauma surgery during the COVID-19 peak was 96%. The rate of any complication was more significant in those presenting with active COVID-19 infections who had sustained potentially life threatening injuries and were over 70 years of age. Conversely those without active COVID-19 infection and who lacked significant co-morbidities experienced a lower complication and mortality rate. Highlights: 22% of the population were COVID-19 positive at any time point. The overall mortality and complication rates for the population were 4% and 14% respectively. Complication rates were higher in those who were COVID-19 positive, over 70 with hip fractures. Conversely those who were under 70 and COVID-19 negative had lower complication rates.